Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00127-010-0336-6
|View full text |Cite
|
Sign up to set email alerts
|

Attempted suicide among immigrants in European countries: an international perspective

Abstract: The similarity of most immigrant groups' SARs across centres, and the correlation with suicidality in the countries of origin suggest a strong continuity that can be interpreted in either cultural or genetic terms. However, the generally higher rates among immigrants compared to host populations and the similarity of the rates of foreign-born and those immigrants who retained the citizenship of their country of origin point to difficulties in the acculturation and integration process. The positive correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 51 publications
5
51
2
1
Order By: Relevance
“…[15] In an international study, 27 out of the 56 immigrant groups are shown to have higher suicide attempt rates than their host country counterparts, with only four groups having significantly lower rates. [34] This suggests the importance of understanding differences across immigrant groups and by age of arrival.…”
Section: Overview Of Risk and Protective Factorsmentioning
confidence: 99%
“…[15] In an international study, 27 out of the 56 immigrant groups are shown to have higher suicide attempt rates than their host country counterparts, with only four groups having significantly lower rates. [34] This suggests the importance of understanding differences across immigrant groups and by age of arrival.…”
Section: Overview Of Risk and Protective Factorsmentioning
confidence: 99%
“…Generation and time in the U.S. appear to influence the risk for suicidality among Latinos [9-11], with SI highest in US-born Latinos, followed by immigrants who migrated as children (<=12 years) [4, 12]. This posits an association of acculturation and time in the US with suicidality [13].…”
Section: Introductionmentioning
confidence: 99%
“…Endorsement of acculturative stress has been associated with over three times increased odds of suicide attempts among Latino emerging adults in the U.S. [14]. A study of immigrants in European countries showed that 27 out of 56 groups studied had higher rates of suicide attempts when compared to the host population and to their counterparts who had not migrated [9]. In a separate study in the Netherlands, living in a neighborhood with high minority density was associated with lower rates of suicide among non-Western immigrants when compared to native Dutch residents [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a small study of Black youth aged 18–24 ( N = 250), Castle et al [48] reported that acculturation was positively associated with suicidal ideation. Similarly, elevated rates of attempted suicide among racial/ethnic minority immigrants in European countries may indicate difficulties in the acculturation and social integration process [49]. Crawford et al [50] found that suicide attempts were more common among women in certain minority groups compared to White and native samples in the UK.…”
Section: Discussionmentioning
confidence: 99%